2017
DOI: 10.1016/j.cobme.2017.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Central nervous system microstimulation: Towards selective micro-neuromodulation

Abstract: Highlights: • Electrical microstimulation to modulate neural activity has emerged as a critical tool in brain research, neurotherapeutics, and bidirectional neuroprostheses. • Recent successes in sensory, motor, auditory, visual, and cognitive neuroprostheses demonstrate a need for more focal micro-neuromodulation technologies. • Advances in electronics, optics, and magnetics are leading towards stable, high spatialresolution interfaces. • Advances in neuroprosthetic technologies may one day enable single neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 189 publications
0
9
0
Order By: Relevance
“…Microelectrode recordings of single-units have revealed fundamental basic neurophysiology of subcortical structures, but continued LFP characterization of non-motor processing remains critical for clinical translation. For instance, macroelectrodes implanted in the basal ganglia for movement and neuropsychiatric disorders reliably record LFPs—not single-units—and their electrophysiological capabilities are more resistant to the foreign body response (Vetter et al, 2004 ; Koivuniemi et al, 2011 ; Urdaneta et al, 2017 ; Wong et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Microelectrode recordings of single-units have revealed fundamental basic neurophysiology of subcortical structures, but continued LFP characterization of non-motor processing remains critical for clinical translation. For instance, macroelectrodes implanted in the basal ganglia for movement and neuropsychiatric disorders reliably record LFPs—not single-units—and their electrophysiological capabilities are more resistant to the foreign body response (Vetter et al, 2004 ; Koivuniemi et al, 2011 ; Urdaneta et al, 2017 ; Wong et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Beyond basic neuroscience investigation, this line of work has important clinical implications for a wide range of neurological and psychiatric disorders. For instance, it may elucidate the observed improvements or deteriorations in non-motor symptoms seen after DBS for a broad range of FDA-approved and experimental uses (Parsons et al, 2006 ), and offer insights for more selective neuromodulation therapies (Urdaneta et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Clinical work has shown that ICMS of somatosensory cortex (S1) can elicit touch percepts in patients with paralysis ( Flesher et al, 2016 ). The use of implantable microelectrodes allows for the spatial selectivity ( Urdaneta et al, 2017 ) necessary to elicit naturalistic touch percepts in specific areas of the arm ( Salas et al, 2018 ) or individual fingers ( Flesher et al, 2016 ). While this is encouraging, the widespread implementation of ICMS technologies for chronic use requires further understanding of the challenges inherently associated with implantable microelectrodes, such as the foreign body response (FBR) ( Biran et al, 2005 ) and the long-term stability of ICMS.…”
Section: Introductionmentioning
confidence: 99%
“…In order to monitor and control the brain activity, control units that are able to translate the natural signals from brain into understandable machine commands (i.e., Brain-Machine Interfaces -BMIs) has been developed in the past years [47]. BMIs are conceived as a new treatment method or therapy for neural diseases, and cognitive abilities problems [48]. For instance, patients with the loss of somatosensation, (i.e., tactile sensation) suffer from the serious deficits in motor control or struggle to manipulate objects using prosthesis, can be treated with neurostimulation using BMIs.…”
Section: Nervous and Neural Interfacesmentioning
confidence: 99%